NADPH Oxidase Regulates the Growth and Pathogenicity of Penicillium expansum - Zhang, Xuemei; Zong, Yuanyuan; Gong, Di; Yu, Lirong; Sionov, Edward; Bi, Yang; Prusky, Dov (Frontiers in Plant Science, 2021)
The occurrence of reactive oxygen species during colonization of necrotrophic pathogens attacking fruit are critical tools for their attack but it's importance for Penicillium expansum was not conclude. This study aimed to understand the regulatory effects of NADPH oxidase (Nox) genes on the growth and pathogenicity of P. expansum in apple fruit. Deletion mutants of ΔPeNoxA, ΔPeNoxR, and ΔPeRacA genes were obtained to determine the contribution to the colonization process. While the ΔPeRacA showed a significant effect on the reduction of growth and pathogenicity, the ΔPeNoxA strain negatively regulated growth and development of P. expansum and did not show any significant effect on the pathogenicity, and the ΔPeNoxR showed no effect on growth or pathogenicity on apple fruit. However, analysis of the content of O2·-and H2O2 in the mycelium of all the Nox mutants showed a significant reduction, confirming the functionality of the Nox mutations. Growth under stress conditions in the presence of Congo Red, sodium lauryl sulfate and H2O2 showed a negative effect on the radial growth of ΔPeNoxA. But a positive effect on radial growth reduction by ΔPeNoxR and ΔPeRacA mutants. Interestingly, the host antioxidant activities levels of SOD and CAT in fruits after inoculation with ΔPeNoxA, ΔPeNoxR, and ΔPeRacA mutants declined suggesting the reduced reactive oxygen species accumulation the colonized region. Present results suggest that PeNoxA, PeNoxR and PeRacA genes differentially regulated the growth and pathogenicity of P. expansum by producing reactive oxygen species, while PeRacA gene showed the strongest regulation effect.